KONSEP PENDIDIKAN MORAL MENURUT AL-GAZALI DAN ÃMILE DURKHEIM - Ratna, Ratna (UIN Alauddin Makassar, 2015)
Abstract: The development of science and technology has brought about many changes in society life. However, the main concern here is that the changes have caused the existence of moral crisis. This is based on the fact that the development of knowledge in the area of technology and information is not balanced with the development of moral of modern society. The reality of life that drives educaÂtional activity continuously to run and change that demand the new acceleration in educational world, especially moral education. Therefore, the concept of moral education still needs to be specifically examined because the concept of moral education is very important in educational world. Moral education is not a new problem. There are many experts that have formulated the concept of education and have taken moral as not a separated part of educational system. Even, moral education has to integrate the spiritual and intelectual aspects and also normatifÂ and hystorical aspects (reality). The integration of all these aspects will become the core for the balance between the aspects of cognitive (mind), affective (faith), and pychomotoric (deed) in education practices.Abstrak: Perkembangan sains dan teknologi telah banyak memberi perubahan dalam kehidupan masyarakat. Tetapi, yang memprihatinkan adalah perubahan itu justru mendorong munculnya krisis moral. Hal ini didasarkan pada kenyataan bahwa kemajuan ilmu pengetahuan di bidang teknologi dan informasi tidak selalu sebanding dengan kemajuan di bidang moral pada masyarakat modern. Realitas kehidupan yang menggiring aktivitas pendidikan terus berjalan dan berubah-ubah menuntut adanya suatu akselerasi baru dalam dunia pendidikan terkhusus pendidikan moral. Oleh karena itu, konsep pendidikan moral masih perlu dikaji secara spesifik karena konsep pendidikan moral adalah hal yang sangat penting dalam dunia pendidikan. Pendidikan moral memang bukanlah persoalan baru. Banyak ahli pendidikan telah merumuskan konsep pendidikan dan menjadikan moral sebagai bagian yang tidak terpisahkan dari sistem pendiÂdikan. Bahkan pendidikan moral harus mampu mengintegrasikan aspek-aspek spiritual dan intelektual serta aspek normativitas dan historitas (realitas). Integrasi keseluru-han aspek tersebut akan menjadi inti bagi keseimbangan aspek kognitif, (akal), afektif (iman), dan psikomotorik (amal) dalam pendidikan secara praktis.